2018
DOI: 10.1186/s13071-018-2647-5
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis in Sri Lanka: spatial distribution and seasonal variations from 2009 to 2016

Abstract: BackgroundLeishmaniasis is listed as one of the eight neglected tropical diseases by the World Health Organization and the number of cases in endemic areas has seen a sharp rise in the past decade. More alarmingly, reports have shown that leishmaniasis is spreading to non-endemic areas of the world due to co-infection with HIV. In Sri Lanka, leishmaniasis is considered as a notifiable disease from 2008 and has seen a rising trend of incidence since then. This is the first study describing the burden, seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…Leishmaniasis has now been identi ed as an emerging disease in Sri Lanka (14). Emphasizing the need for controlling this disease Ministry of health, Sri Lanka declared it as a noti able disease in 2008 (15). As expected, doctors were more knowledgable about the clinical features, causative organism, disease transmission and the vector of Leishmaniasis compared to the studies done in general public (16,17).…”
Section: Discussionmentioning
confidence: 97%
“…Leishmaniasis has now been identi ed as an emerging disease in Sri Lanka (14). Emphasizing the need for controlling this disease Ministry of health, Sri Lanka declared it as a noti able disease in 2008 (15). As expected, doctors were more knowledgable about the clinical features, causative organism, disease transmission and the vector of Leishmaniasis compared to the studies done in general public (16,17).…”
Section: Discussionmentioning
confidence: 97%
“…Our ndings indicate that there is spatial expansion of CL transmission in Sri Lanka involving hitherto non-endemic regions in the wet zone of the country. The districts of Anuradhapura, and Polonnaruwa in the North Central province, and Hambantota in the Southern province of Sri Lanka were the initial hotspots of CL [24]. More recently (2014-2016), the district of Kurunegala in the North Western province has become a major hotspot for CL [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of CL have been documented throughout the country, the large majority (over 90%) is usually from the North Central, North Western and Southern provinces [24]. A very low number of cases have been identi ed in the Western province, which includes Colombo, Gampaha and Kalutara districts [24]. Thus, CL was an infrequent infection in the district of Gampaha until recently.…”
mentioning
confidence: 99%
“…20 A seasonal trend of leishmaniasis was found in a study which evaluated the data available from 2009 to 2016 and a peak was shown in the period between July to September in the north-central region and in October to December in the southern region. 21…”
Section: Review Of Existing Literature On Leishmaniasis Risk Factors mentioning
confidence: 99%